Innovation activity of enterprises in Lviv region - Tsogla, О. О. (Видавництво Львівської політехніки, 2016)
The article analyzes the innovative activity of industrial enterprises of Lviv and found that the main factors hampering business in the field of innovation, there is a limited amount, and in some places, and the lack of innovation funding from the state budget, the lack of economic incentives for attracting investment resources in innovation processes, the uncertainty of the institutional environment for the development of innovation infrastructure (technology parks, techno, technology transfer centers, etc.). Determined that the competitiveness of Lviv region depends on the ability to innovate, modernize production processes and to adapt to changing environmental conditions. Проаналізовано інноваційну активність промислових підприємств Львівщини та виявлено, що основні чинники, які гальмують ведення бізнесу у сфері інноваційної діяльності, є обмежений обсяг і відсутність фінансування інноваційної діяльності з Державного бюджету, брак економічних стимулів щодо залучення інвестиційних ресурсів в інноваційні процеси, невизначеність інституційних умов для розвитку інноваційної інфраструктури (технопарків, технополісів, центрів трансферу технологійта ін.). Визначено, що конкурентоспроможність Львівського регіону залежить від здатності впроваджувати інновації, модернізувати виробничі й технологічні процеси, пристосовуючись до змінних умов навколишнього середовища.
Інноваційна активність промислових підприємств Львівщини
Keywords: innovative development; regional features; innovative activity of industrial enterprises; innovative costs; innovative products; інноваційний розвиток; регіональні особливості; інноваційна активність промислових підприємств; інноваційні витрати; інноваційна продукція